Looking for leadership: the potential of dialogic reflexivity with rural early-career teachers. Issue 7 (3rd October 2017) - Willis, Jill; Crosswell, Leanne; Morrison, Chad; Gibson, Andrew; Ryan, Mary
Abstract: Many early-career teachers (ECTs) begin their teaching careers in rural and remote schools in Australia, and do not stay long, with consequences for their own lives, and for their students, schools and communities. By understanding how first-year ECTs navigate personal (subjective) and contextual (objective) conditions, opportunities to disrupt patterns of ECT attrition may be found. This paper explores the online longitudinal reflections from two rural ECTs. Margaret Archer's three dimensions of reflexivity were used to analyse what personal, structural and cultural resources were activated by ECTs as they discerned and deliberated the costs of being a rural ECT. The potential for school leaders and mentors to support rural ECTs through dialogic reflexivity, that is the opportunity to discern and deliberate priorities with others, is identified as a role that is significant for ECT support but not straightforward. Prompts for dialogic reflexivity are proposed.